2015
DOI: 10.1039/c5ce00036j
|View full text |Cite
|
Sign up to set email alerts
|

Phase transition studies of dutasteride crystalline forms

Abstract: Three crystalline forms of dutasteride, known in the literature as forms I, II and III, were studied. It has been proved that only form I is an unsolvated form. Both forms II and III are hydrates (pseudopolymorphs).Phase transition studies performed by thermoanalytical techniques and variable temperature PXRD measurements, in the temperature region from 30 to 180°C, revealed that dehydration leads to an unstable phase, which finally transforms into form I. Details of the crystal and molecular structure of form… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…The study was confirmed by powder X-ray diffraction (XRD-6000, Shimadzu, Japan 220V/50Hz) at a continuous scan range of 2θ = 5 -80º. 26…”
Section: Powder X-ray Diffraction (Xrd) Studiesmentioning
confidence: 95%
“…The study was confirmed by powder X-ray diffraction (XRD-6000, Shimadzu, Japan 220V/50Hz) at a continuous scan range of 2θ = 5 -80º. 26…”
Section: Powder X-ray Diffraction (Xrd) Studiesmentioning
confidence: 95%
“…Other methods, including e.g. differential scanning calorimetry (DSC), thermogravimetric analysis (TGA) as well as Raman (RS) and infrared spectroscopes (IR), help to further characterize the crystalline and amorphous forms.In this presentation, a few examples of phase transition studies in the active substances and solid dosage forms will be discussed: structural and physicochemical studies of olopatadine hydrochloride conformational polymorphs, phase transitions of dutasteride performed by the VT-XRPD method [2], erlotynib polymorphism studies performed by means of RS and the evaluation of analytical methods for the detection of phase transitions in tablets containing aripiprazole [3] and imatinib [4]. …”
mentioning
confidence: 99%